EFEKTIVITAS KONSELING KELOMPOK SOLUTION FOCUSED BRIEF COUNSELING UNTUK MENINGKATKAN SELF-EFFICACY KARIER SISWA KELAS XII SMAN MODEL TERPADU BOJONEGORO - Dwi Ratnawati Wahyuningsih; Denok Setiawati; Wiryo Nuryono (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
One counseling approach that can be applied by counselors to enhance students’ career self-efficacy by utilizing their strengths and personal resources is group counseling using the Solution-Focused Brief Counseling (SFBC) approach. This study aimed to examine the effectiveness of Solution-Focused Brief Counseling group counseling in improving the career self-efficacy of Grade XII students at SMAN Model Terpadu Bojonegoro. The study employed a quasi-experimental design using a nonequivalent control group design. The research participants consisted of 18 students, including 9 students in the experimental group and 9 students in the control group, selected through a non-random purposive sampling technique. Data were collected using a career self-efficacy questionnaire. The implementation of Solution-Focused Brief Counseling group counseling was conducted in four sessions, which include rapport building, problem identification, counseling goal setting, intervention implementation, termination, evaluation, and follow-up. The results of data analysis showed that the experimental group achieved a posttest mean score of 88.67, while the control group obtained a posttest mean score of 81.67. These findings indicate a significant difference between the two groups, with a higher increase in career self-efficacy observed in the experimental group compared to the control group. Furthermore, the independent samples t-test revealed a significance value (2-tailed) of 0.005, which is lower than the significance level of 0.05. This result indicates that Solution-Focused Brief Counseling (SFBC) group counseling is effective in improving the career self-efficacy of Grade XII students at SMAN Model Terpadu Bojonegoro.